Politeness Value Adoption from Petitih Minangkabau Proverbs on Bibliocounseling as KIPAS Counseling Model - Ibrahim Ali Husein; Andi Mappiare-AT; Fattah Hanurawan (Pascasarjana UM, 2020)
Abstract: The purpose of this research was to identify and describe about the value of politeness in pepatah petitih Minangkabau. This research used a descriptive apporoach using with analysis strategi of Gadamerian hermeneutic. The results of the identification value are then adopted into a format and content of bibliocounseling to develop social skills of students’. The result of analysis showed that there were 7 (seven) values of politeness in pepatah petitih Minangkabau. These value are summarized into 4 (four) elements of social skills to the conception of kato nan ampek. The stage activity bibliocounseling was based on the stege of the counseling model of KIPAS which consists of good news, data interation or internalization, planning of action, actualization of planning, and celebration.Key words: politeness value, Pepatah Petitih Minangkabau, bibliocounsellng, KIPAS counseling modelAbstrak: Penelitian ini bertujuan untuk mengidentifikasi dan mendeskripsikan nilai kesopanan dalam pepatah petitih Minangkabau. Penelitian ini menggunakan pendekatan kualitatif yang bersifat deskriptif dengan menggunakan strategi analisis hermeneutika Gadamerian. Hasil dari identifikasi nilai tersebut kemudian diadopsi menjadi format dan isi bibliokonseling untuk mengembangkan kecakapan sosial siswa. Hasil analisis menunjukkan terdapat 7 (tujuh) nilai kesopanan dalam pepatah petitih Minangkabau. Nilai tersebut terangkum ke dalam 4 (empat) unsur kecakapan sosial menurut konsep kato nan ampek. Tahap kegiatan bibliokonseling mengacu pada tahapan konseling model KIPAS yang terdiri dari kabar gembira, integrasi data atau internalisasi, perencanaan tindakan, aktualisasi rencana, dan selebrasi.Kata kunci: nilai kesopanan, Pepatah Petitih Minangkabau, bibliokonseling, model konseling KIPAS